Commonwealth Power Over Higher Education: implications and realities - Craven, Greg (John Curtin Institute of Public Policy, 2006)
This paper explores the Commonwealth's power over universities. First it considers the extent of Commonwealth constitutional power as a matter of strict law and second it considers that constitutional power within a wider legal, administrative and practical context. The paper reaches four general conclusions: (i) the Commonwealth enjoys significant direct constitutional power over higher education; (ii) the Commonwealth has significant power to influence and form higher education policy indirectly through conditional funding of universities; (iii) notwithstanding its direct legislative power and its capacity for indirect financial influence, critically the Commonwealth presently lacks the cohesive constitutional power necessary to regulate the universities directly and comprehensively, although this may change in light of an impending decision of the High Court; (iv) in light of this analysis, any genuine attempt at national higher education legislation or regulation by the Commonwealth would, at present, have to be based upon significant cooperation with the States.